Resilience Assessment Scale for the Prediction of Suicide Reattempt in Clinical Population - Sánchez-Teruel, David; Robles-Bello, María Auxiliadora; Muela-Martínez, José Antonio; García-León, Ana (Frontiers in Psychology, 2021)
The objective of this work was to construct and validate an instrument for assessing resilience to suicide attempts in a Spanish clinical population that has made a previous attempt, and to verify its efficacy for predicting future suicide reattempts at six months. For the construction of a Scale of Resilience to Suicide Attempts (SRSA) the theoretical-rational strategy was used. The constructed SRSA-18 consisted of 18 items and 3 subdimensions (internal and external protection and emotional stability), had high internal consistency (α = .88; ω = .89) and a high positive correlation with the Suicide Resilience Inventory-25, SRI-25 (r = .91; p < .01), and to a lesser extent with general resilience scales such as the Connor-Davidson Resilience Scale, CD-RISC (r = .79; p < .01) and the Resilience Scale of 14 items, RS-14 (r = .76; p < .01). Additionally, a specific SRSA-18 score predicted future suicide reattempts six months after the first attempt. This new scale (SRSA-18) assesses in a brief and rapid way, through protective factors rather than risk factors, the level of resilience to the suicide attempt in specific clinical subpopulations in hospital emergency services, being able to prevent suicide reattempts with higher lethality.